Synthesis of acrylic acid from methyl lactate over calcium phosphate catalysts in a fixed bed reactor: time-on-stream behavior and kinetic analysis - Aho, Atte (Taylor & Francis, 2025)
Transformation of methyl lactate to acrylic acid was investigated over Ca3(PO4)2, Ca2(P2O7) and their mixture in the temperature range of 250-425 °C. The initial concentration of methyl lactate in water was varied from 2 wt% to neat methyl lactate. The results showed that these phosphate catalysts did not contain any measurable amounts of either acid sites or basic sites. The best catalyst was Ca3(PO4)2 giving 62% selectivity to acrylic acid at 75% conversion at 400 °C using GHSV of 95280 h−1 and 2 wt% methyl lactate in the initial feed. This catalyst exhibited larger surface area in comparison to Ca2(P2O7). Elemental analysis revealed that some Ca leaching occurred during reaction, while in case of Ca2(P2O7) the calcium leaching was 3.4 fold higher than observed for Ca3(PO4)2. Long-term results over Ca3(PO4)2 showed that extensive catalyst deactivation occurred during the first 11 h time-on-stream, after which the activity dropped only slightly. In addition to kinetic studies with different parameters, also, kinetic modeling was performed and the activation energies for formation of different products were determined over different catalysts.